The Role of Fasting Dalailul Qur'an in Shaping Shoim's Personality : Study at Pesantren Bustanu Usysyaqil Qur’an Gading, Semarang Regency - Aufa Abdillah (Journal of Nahdlatul Ulama Studies, 2021)
Fasting dalail Qur'an is a practice carried out by santri at BUQ Gading Islamic Boarding School, which is a special takhfidz al-Qur'an. Fasting is carried out for one year with a qomariyah count and the performers are obliged to complete one juz (chapter) in one day. Santri BUQ are strongly encouraged to practice fasting as a form of riyadhoh fasting so that santri have a personality that is able to control things that are harmful, not useful, and things that are prohibited by religion. The research method used in this study is descriptive qualitative with a phenomenological approach. The results of the study show that santri who practice fasting in the Qur'an are able to form a shoim personality, that is able to control themselves well so as not to do actions, words and attitudes that are detrimental to both themselves and others.